Development of a Pin Diode-Based Beam-Switching Single-Layer Reflectarray Antenna. (29th December 2020) - Abbasi, Muhammad Inam; Ismail, Muhammad Yusof; Kamarudin, Muhammad Ramlee
Abstract : This paper presents a practical demonstration for the design and development of a switchable planar reflectarray using PIN diodes in the X-band frequency range. Waveguide scattering parameter measurements for the unit cells and far-field measurements of the periodic reflectarrays have been carried out to verify the predicted results. Reflectarray unit cell measurements demonstrated a frequency tunability of 0.36 GHz with a dynamic phase range of 226°. On the other hand, the designed 6 × 6 periodic reflectarray has been shown to achieve beam switching from +6° to −6° with different switching states of PIN diodes. This type of beam switching can be used in satellite communication for specific region coverage.